2012
DOI: 10.1007/s10853-012-6434-y
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide 6 composites reinforced with glass fibers modified with electrostatically assembled multiwall carbon nanotubes

Abstract: Glass fiber-multiwall carbon nanotubes (GFMWCNTs) hybrid preforms were prepared by electrostatic assembly method. Negatively charged MWCNTs by oxidization treatment were directly adsorbed onto the surfaces of positively charged GF to form tunable structure. The thickness and morphology of GF-MWCNTs preforms can be controlled by the assembly pH value and the concentration of oxidized-MWCNTs solution. We demonstrate that GF-MWCNTs preforms have uniform and porous interconnected network structure of MWCNTs on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A variety of techniques have been investigated to deposit MCNTs onto the fiber surface, such as chemical vapor deposition (CVD), 23 electrophoretic deposition (EPD), 24 spray-up, 25 using sizing coating, 26 electrostatic layer-by-layer assembly, 27 etc. In particular, the CVD and EPD techniques have been extensively used to create the multiscale preform, which was applied to fabricate a multiscale composite through the hand-made or mold press or VARTM process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of techniques have been investigated to deposit MCNTs onto the fiber surface, such as chemical vapor deposition (CVD), 23 electrophoretic deposition (EPD), 24 spray-up, 25 using sizing coating, 26 electrostatic layer-by-layer assembly, 27 etc. In particular, the CVD and EPD techniques have been extensively used to create the multiscale preform, which was applied to fabricate a multiscale composite through the hand-made or mold press or VARTM process.…”
mentioning
confidence: 99%
“…31 Therefore, it is highly desirable to make a uniformly distributed MCNT/GF preform by a simple and practical method for making multiscale composites based on the resin transfer molding process. Furthermore, the GF tows 32 or chopped GFs, 27 or even single fiber, 20 were usually used as the substrate to deposit MCNTs. A few researchers have tried to deposit MCNTs onto the woven GF fabric surface.…”
mentioning
confidence: 99%
“…Therefore, electrostatic absorption can be realized because of the opposite charges of MWCNTs and GFs. Based on our previous work , the extent of protonation of NH 2 group on GF surfaces increased as with decreasing pH; thus, lower pH value provided higher charge densities of –NH 3 + , the deposited MWCNTs were proved to be more densely compacted at pH 5 than at pH 7.…”
Section: Resultsmentioning
confidence: 82%
“…In another study, 30% enhancement in the storage modulus was shown to be possible by the addition of MWCNTs into the Polyamide 6 (PA 6)/Glass Fiber (GF) composites because of the interconnecting effect of MWCNTs within the thermoplastic matrix. Another outcome of the interconnecting effect was reported to be greater T g , measured from the temperature curves of MWCNT-reinforced composites [16]. Jin et al also stated a similar, increasing behavior for E' and T g by the addition of CNTs, showing a stiffening effect at high temperatures [17].…”
Section: Introductionmentioning
confidence: 91%